Resting state functional connectivity of the subthalamic nucleus in Parkinson's disease assessed using arterial spin‐labeled perfusion fMRI - Fernández‐Seara, María A. (John Wiley and Sons Inc., 2015)

(untitled) (Hum Brain Mapp)
Neurophysiological changes within the cortico‐basal ganglia‐thalamocortical circuits appear to be a characteristic of Parkinson's disease (PD) pathophysiology. The subthalamic nucleus (STN) is one of the basal ganglia components showing pathological neural activity patterns in PD. In this study, perfusion imaging data, acquired noninvasively using arterial spin‐labeled (ASL) perfusion MRI, were used to assess the resting state functional connectivity (FC) of the STN in 24 early‐to‐moderate PD patients and 34 age‐matched healthy controls, to determine whether altered FC in the very low frequency range of the perfusion time signal occurs as a result of the disease. Our results showed that the healthy STN was functionally connected with other nuclei of the basal ganglia and the thalamus, as well as with discrete cortical areas including the insular cortex and the hippocampus. In PD patients, connectivity of the STN was increased with two cortical areas involved in motor and cognitive processes. These findings suggest that hyperconnectivity of the STN could underlie some of the motor and cognitive deficits often present even at early stages of the disease. The FC measures provided good discrimination between controls and patients, suggesting that ASL‐derived FC metrics could be a putative PD biomarker. Hum Brain Mapp 36:1937–1950, 2015. © 2015 Wiley Periodicals, Inc.